Expression and functional analysis of a transgenic cytochrome P450 monooxygenase in Pueraria mirifica - Li, Xu; Ruethaithip Kaopong,; Sureeporn Nualkaew,; Arthiya Chullasara,; Amornrat Phongdara, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Isoflavonoids are the main compound in White Kwao Krua (Pueraria mirifica), which is an effective folk medicinal plant endemic to Thailand. It has been widely used for improving human physical and treating diseases. There are substances with estrogenic activities have been isolated from P. mirifica, such as puerarin, daidzein and genistein. Isoflavone synthase (IFS) is one of the key enzymes in Leguminous plants to convert liquiritigenin, liquiritigenin C-glucoside and naringenin chalcone to isoflavonoids. The aim of this research was to enhance the production of isoflavonoids by metabolic engineering. Transgenic plants were constructed by introducing P450 gene (EgP450) which is similar to IFS from oil palm (Elaeis guineensis), into P. mirifica by a biolistic method. After the transgenic plants had proved successfully, isoflavonoids of each group plants were determined by HPLC. The contents of daidzein and genistein in transgenic plants were higher than the control plants.